Cutinase promotes dry esterification of cotton cellulose - Zhao, X. (2016)
Cutinase from Thermobifida fusca was used to esterify the hydroxyl groups of cellulose with the fatty acids from triolein. Cutinase and triolein were pre-adsorbed on cotton and the reaction proceeded in a dry state during 48 hours at 35ºC. The cutinase-catalyzed esterification of the surface of cotton fabric resulted in the linkage of the oleate groups to the glycoside units of cotton cellulose. The superficial modification was confirmed by performing ATR-FTIR on treated cotton samples and by MALDI-TOF analysis of the liquors from the treatment of the esterified cotton with a crude cellulase mixture. Modified cotton fabric also showed a significant increase of hydrophobicity. This work proposes a novel bio-based approach to obtain hydrophobic cotton. This article is protected by copyright. All rights reserved.